2022
DOI: 10.2147/jpr.s338691
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life and Pain: The Differential Effects of Coherence, Purpose, and Mattering on Pain Severity, Frequency, and the Development of Chronic Pain

Abstract: Objective Meaning in life is consistently associated with better health outcomes across a range of mental and physical domains. However, meaning in life is a complex construct involving three distinct facets: coherence, purpose, and mattering. While these facets have been studied individually in relation to pain, they have not been assessed concurrently to parse out their potential distinct contributions to pain outcomes. We sought to identify the unique relationships of these individual facets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In line with prior literature (Furrer et al, 2019;Sta ˚lnacke, 2011;Larsson et al, 2019;Fisher et al, 2004;Achat et al, 2000;Boring et al, 2022), the current study extends previous findings by showing that higher levels of mental well-being predict lower odds for pain and functional impairment due to pain one year later. The results were significant after adjusting for a range of sociodemographic and health-related factors, as well as depression based on the PHQ-8.…”
Section: Contextualization and Implications For Policy And Practicesupporting
confidence: 92%
See 1 more Smart Citation
“…In line with prior literature (Furrer et al, 2019;Sta ˚lnacke, 2011;Larsson et al, 2019;Fisher et al, 2004;Achat et al, 2000;Boring et al, 2022), the current study extends previous findings by showing that higher levels of mental well-being predict lower odds for pain and functional impairment due to pain one year later. The results were significant after adjusting for a range of sociodemographic and health-related factors, as well as depression based on the PHQ-8.…”
Section: Contextualization and Implications For Policy And Practicesupporting
confidence: 92%
“…Larsson et al (2019) conducted a prospective study on a population-based cohort in Sweden, and showed that higher levels of hedonic well-being and life satisfaction were associated with lower risk of severe pain two years after baseline. More recently, Boring et al (2022) analyzed a cohort of American adults, and found that sense of coherence – a component of meaning in life – was associated with lower odds of developing pain nine years after baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that the pain dimensions were negatively related to presence of meaning, while positively related to search for meaning, which also verifies the hypothesis. While the former result seems quite reasonable, that is, patients in severe pain show difficulties in achieving life goals and discovering meaning and purpose, 14,34 the latter result is rather thought‐provoking. It may indicate that, despite experiencing a spectrum of pervasive pain symptoms, patients do not abandon their pursuit of goals and aspirations, but search for meaning and purpose in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the longitudinal relationships between chronic pain and PTSD relevant to existential anxiety is scant. In addition to Boring et al, (2022) mentioned above, in a sample of 273 patients with chronic pain, Dezutter et al (2015) found that meaning in life at Time 1 predicted depressive symptoms at Time 2 (but not pain intensity) and that pain medication at Time 2 (but not pain intensity) predicted the presence of meaning at Time 3 (Dezutter et al, 2015).…”
Section: The Integrated Model Of Co-occurring Chronic Pain and Ptsdmentioning
confidence: 92%